Solve for x
x=13
x=5
Graph
Share
Copied to clipboard
\left(\sqrt{2x-1}-2\right)^{2}=\left(\sqrt{x-4}\right)^{2}
Square both sides of the equation.
\left(\sqrt{2x-1}\right)^{2}-4\sqrt{2x-1}+4=\left(\sqrt{x-4}\right)^{2}
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(\sqrt{2x-1}-2\right)^{2}.
2x-1-4\sqrt{2x-1}+4=\left(\sqrt{x-4}\right)^{2}
Calculate \sqrt{2x-1} to the power of 2 and get 2x-1.
2x+3-4\sqrt{2x-1}=\left(\sqrt{x-4}\right)^{2}
Add -1 and 4 to get 3.
2x+3-4\sqrt{2x-1}=x-4
Calculate \sqrt{x-4} to the power of 2 and get x-4.
-4\sqrt{2x-1}=x-4-\left(2x+3\right)
Subtract 2x+3 from both sides of the equation.
-4\sqrt{2x-1}=x-4-2x-3
To find the opposite of 2x+3, find the opposite of each term.
-4\sqrt{2x-1}=-x-4-3
Combine x and -2x to get -x.
-4\sqrt{2x-1}=-x-7
Subtract 3 from -4 to get -7.
\left(-4\sqrt{2x-1}\right)^{2}=\left(-x-7\right)^{2}
Square both sides of the equation.
\left(-4\right)^{2}\left(\sqrt{2x-1}\right)^{2}=\left(-x-7\right)^{2}
Expand \left(-4\sqrt{2x-1}\right)^{2}.
16\left(\sqrt{2x-1}\right)^{2}=\left(-x-7\right)^{2}
Calculate -4 to the power of 2 and get 16.
16\left(2x-1\right)=\left(-x-7\right)^{2}
Calculate \sqrt{2x-1} to the power of 2 and get 2x-1.
32x-16=\left(-x-7\right)^{2}
Use the distributive property to multiply 16 by 2x-1.
32x-16=x^{2}+14x+49
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(-x-7\right)^{2}.
32x-16-x^{2}=14x+49
Subtract x^{2} from both sides.
32x-16-x^{2}-14x=49
Subtract 14x from both sides.
18x-16-x^{2}=49
Combine 32x and -14x to get 18x.
18x-16-x^{2}-49=0
Subtract 49 from both sides.
18x-65-x^{2}=0
Subtract 49 from -16 to get -65.
-x^{2}+18x-65=0
Rearrange the polynomial to put it in standard form. Place the terms in order from highest to lowest power.
a+b=18 ab=-\left(-65\right)=65
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as -x^{2}+ax+bx-65. To find a and b, set up a system to be solved.
1,65 5,13
Since ab is positive, a and b have the same sign. Since a+b is positive, a and b are both positive. List all such integer pairs that give product 65.
1+65=66 5+13=18
Calculate the sum for each pair.
a=13 b=5
The solution is the pair that gives sum 18.
\left(-x^{2}+13x\right)+\left(5x-65\right)
Rewrite -x^{2}+18x-65 as \left(-x^{2}+13x\right)+\left(5x-65\right).
-x\left(x-13\right)+5\left(x-13\right)
Factor out -x in the first and 5 in the second group.
\left(x-13\right)\left(-x+5\right)
Factor out common term x-13 by using distributive property.
x=13 x=5
To find equation solutions, solve x-13=0 and -x+5=0.
\sqrt{2\times 13-1}-2=\sqrt{13-4}
Substitute 13 for x in the equation \sqrt{2x-1}-2=\sqrt{x-4}.
3=3
Simplify. The value x=13 satisfies the equation.
\sqrt{2\times 5-1}-2=\sqrt{5-4}
Substitute 5 for x in the equation \sqrt{2x-1}-2=\sqrt{x-4}.
1=1
Simplify. The value x=5 satisfies the equation.
x=13 x=5
List all solutions of \sqrt{2x-1}-2=\sqrt{x-4}.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}